ANALISIS KEPUASAN DAN LOYALITAS PELANGGAN PT. SAWAH BESAR FARMA CABANG JAKARTA - Edza Rinaldi; Ujang Sumarwan; Lilik Noor Yuliati (Ekonomi & Bisnis, 2012)
Pharmaceutical distributionindustry competitionis very tightto makethe customershould beunitedinnumberbecause the customeris an assetpharmaceutical distribution company. Customers demandedthe bestservice of deliveryand quality. whilepharmaceutical industrieshave not beenable toserve our customers,so thatthere is a differencebetween what thecustomer wantswith whatcustomersget fromthe company. The aims of this study are to analyze importances and performances factors that contribute to the customers’ satisfaction, and loyalty of PT Sawah Besar Farma, and to formulate the managerial implications towards the increase of its service quality attributes, in order to give the best strategy for quality customer service. Validity and reliability tests are done before analyzing data. The method used are descriptive analysis, Importance Performance Analysis (IPA), Structural Equations Modelling (SEM), Customer Satisfaction Index CSI), and Customer Loyalty Index (CLI). Based on IPA, the attributes that should be improved are: product completeness, the availabilty of stock, and times to delivery. Based on SEM, the dimensions of servqual that give the highest contribution to the customer satisfaction are tangibility, as much as 0,18. It is followed by reliability 0,17, assurance 0,15, responsiveness 0,14, and empathy 0,14. And then based on Customer satisfaction Index (CSI) The company’s customers are generally satisfied is 78 %, and the Customer Loyalty Index is 80 %. The influnce of the customers’satifaction to their loyalty is 81 %. It means that the satisfied customers are loyal to the company. Keywords: PT. Sawah Besar Farma, satisfaction, loyalty, Analysis SEM, IPA, CSI, CLI.